Web-Based Presence Application Development at Pontianak State Polytechnic - Cahyono, Hendro; Hasan, Hasan; Siswanto, Lindung; Sufandi, M. Ridhwan (ELKHA : Jurnal Teknik Elektro, 2021)
The employees' presence is an important factor for an institution, which is relate to discipline and has an impact on the employee's performance.   Therefore, it is necessary to have specific data collection to record presence, absenteeism, and work activities that has done every day so that employee performance record in real-time and proper. There are many ways that can be done to achieve a good presence information system, one of them is using computer and mobile phone technology which is implemented with a website-based presence application. At the Pontianak State Polytechnic, finger print machine used in the presence process system, but it is still lack in efficiency and effectiveness in data collection, data retrieval as well as data recap calculations, which require a relatively long time. Besides, the bigger risk of error and loss of presence data.   Based on problems, a Web-Based Presence Application Development Information System created at the Pontianak State Polytechnic. The research method used in data collection, which includes research methods, interviews and literature. While software development uses a waterfall model which includes requirements analysis, design, coding, testing and implementation. This web-based presence application can provide convenience in the employee presence process, data search and presence recap calculations, and minimize loss and errors in recording employee presence data. Based on web-based presence application testing and evaluation to thirty-four employees of Pontianak State Polytechnic, it stated that the web-based presence application is suitable for used by all employees of Pontianak State Polytechnic.